HTLV-1-associated adult T cell leukemia is highly susceptible to Navitoclax due to enhanced Bax expression - Witzens-Harig, Mathias; Giaisi, Marco; Köhler, Rebecca; Krammer, Peter H.; Li-Weber, Min (International journal of cancer, 2016)
Over-expression of Bcl-2, Bcl-xL and Bcl-w is frequently associated with cancer resistance to chemotherapy. Navitoclax (ABT-263), an orally bio-available small-molecule mimetic of the Bcl-2 homology domain 3, specifically inhibits Bcl-2, Bcl-xL and Bcl-w. Despite promising results obtained from the clinical trials, the use of Navitoclax in patients is dose-limited due to induction of death of platelets via inhibition of Bcl-xL and subsequent thrombocytopenia. This side effect limits the use of Navitoclax in low doses and to very sensitive tumors. In this study, we show that HTLV-1-associated adult T-cell leukemia/lymphoma (ATL) cells, which over-express Bcl-2, Bcl-xL and Bcl-w, show a 10- to 20-fold higher sensitivity (EC50 = ∼25-50 nM) to Navitoclax compared to non-HTLV-1-associated leukemic cells (EC50 = ∼1 μM). Investigation of the molecular mechanisms revealed that the HTLV-1 oncogenic protein Tax up-regulates expression of the pro-apoptotic protein Bax which enhances the therapeutic efficacy of Navitoclax. In addition, we show that agents that inhibit the transcription elongation or translation initiation such as Wogonin and Roc-A can further decrease the effective dose of Navitoclax. Our study suggests that HTLV-1 ATL may be a good candidate disease for low dose Navitoclax therapy and probably with less risk of thrombocytopenia.